2004
DOI: 10.1002/andp.200410109
|View full text |Cite
|
Sign up to set email alerts
|

SU(3) systematization of baryons: Theoretical methods and mixing with the antidecuplet

Abstract: We take a fresh look at the SU(3) systematization of all known baryons with mass less than 2000 MeV. We describe well-known and new theoretical tools used in grouping elementary particles into unitary multiplets and present the emerging picture of the unitary multiplets and their mixing. The issue of multiplet mixing is discussed in detail with an emphasis on the mixing with the antidecuplet. While SU(3) does not strongly require that the antidecuplet mixes with any established octet or decuplet, it is still p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 23 publications
1
43
0
2
Order By: Relevance
“…For the octet, the center is defined as M 8 = (2m N + 2m Ξ + 3m Σ + m Λ )/8, and for the decuplet it is M 10 = (4m ∆ + 3m Σ * + 2m Ξ * + m Ω )/10 ≈ m Σ * . We take the phenomenological values for M 8 , M 10 from the paper by Guzey and Polyakov [22] who have analyzed baryon multiplets up to 2 GeV.…”
Section: Comparison With the Experimental Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…For the octet, the center is defined as M 8 = (2m N + 2m Ξ + 3m Σ + m Λ )/8, and for the decuplet it is M 10 = (4m ∆ + 3m Σ * + 2m Ξ * + m Ω )/10 ≈ m Σ * . We take the phenomenological values for M 8 , M 10 from the paper by Guzey and Polyakov [22] who have analyzed baryon multiplets up to 2 GeV.…”
Section: Comparison With the Experimental Spectrummentioning
confidence: 99%
“…(57) gives a small χ 2 = 15 MeV. It should be kept in mind, however, that not all members of all multiplets are well established [22], and those that are, have an experimental uncertainty in the masses. It means that the 'experimental' masses for the centers of multiplets are known at best to an accuracy of 20-40 MeV.…”
Section: B Parity-plus Resonancesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mixing of the antidecuplet with three octets with J P = 1/2 + has also recently been investigated phenomenologically in the chiral soliton model where it was assumed that the mixing is small [30]. It was found that this can reduce the size of the widths of the antidecuplet members without much affecting the masses.…”
Section: Representation Mixing In the Fs Modelmentioning
confidence: 99%
“…The success of this assumption was proven in [4,42]. This allows one to make definite predictions for the 10 → B + P transitions in terms of the antidecuplet and octet universal coupling constants.…”
Section: A General Formalismmentioning
confidence: 99%